2018
DOI: 10.7752/jpes.2018.s5300
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Actually, the studies indicate a negative decline dynamics of the main indicators of the physical development and health of the modern young people receiving higher education. In our studies, it was found that the existing physical training programs are not able to provide the optimal level of functional readiness of the military students and officers of the military universities as needed to perform the professional tasks. Moreover, the purpose of research is the search for the optimal training effects aimed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 22 publications
2
23
0
3
Order By: Relevance
“…It can be assumed that the optimal choice of exercises and workout intensity will be the determining factor for in-creasing the workability and physical fitness of practitioners. Kudryavtsev et al indicate that the purposeful use of special exercises (Burpee) effectively increases speed-strength and functional abilities of the future police officers in a relatively short period of time -4-5 weeks (Kudryavtsev et al, 2018). Kolomiitseva et al indicate that using a 12-week CrossFit program was a significant improvement in the physical fitness of cadets (Kolomiitseva et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be assumed that the optimal choice of exercises and workout intensity will be the determining factor for in-creasing the workability and physical fitness of practitioners. Kudryavtsev et al indicate that the purposeful use of special exercises (Burpee) effectively increases speed-strength and functional abilities of the future police officers in a relatively short period of time -4-5 weeks (Kudryavtsev et al, 2018). Kolomiitseva et al indicate that using a 12-week CrossFit program was a significant improvement in the physical fitness of cadets (Kolomiitseva et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The solution to this problem is the successful adaptation of the modern techniques of intensive functional workout in PT curriculum of the cadets and military students (Kudryavtsev et al, 2018). Kolomiitseva et al suggest using the CrossFit training program in PT curriculum of cadets (Kolomiitseva et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In our studies, a positive result was achieved already in 20 weeks of training which can be explained both by a fairly high initial level of preparedness of some of the young people for passing the GTO tests and by the high efficiency of the methods proposed by the authors to increase the level of physical fitness of the young people. It should be noted that the need to use complex PE which has a sufficient duration (from several weeks) and is aimed at enhancing the physical fitness of the young people as the experts note (Campos, Campos, Bezerra, & Pellegrinotti, 2017;Kudryavtsev et al, 2018). Scientists also insist on the need to make changes to the PE process of the student youth and to modernize PE taking into account the implementation of the standards of the GTO sports complex in the activities of the educational organizations (Anishenko et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…At the (2+) level, the circular training was characterized by a greater intensity: the weight of the projectiles was 60-70% maximum, the height of the bollard for jumps was 90-120 cm, the rest after the exercise cycle was reduced to 1-1.5 minutes and the number of cycles was increased to 8-9 in each session. By the way, such trainings are similar in nature of the load and exercises with CrossFit training the effectiveness of which is in raising the level of physical fitness of the students is emphasized by the experts (Kudryavtsev et al, 2018). The load intensity of each training cycle in the EG group is presented in Table 1.…”
Section: Procedurementioning
confidence: 99%
“…Today, many scientists propose introducing various types of aerobic and mixed fitness training into PE practice actively: callanetics (Kolomiytseva, & Anatskyi, 2017), crossfit training (Kudryavtsev, et al, 2018), Kangoo-jumps (Mokrova, et al, 2018). Fortunately, scientists have found that an increase in cardiorespiratory fitness has a positive effect on both the level of physical health and academic performance of young people (Marques, et al, 2018) and urge the active use of aerobic fitness training in the practice of youth education (Symolik, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%